A Comparison of Distractor Selection Among Proficiency Levels in Reading Tests: A Focus on Summarization Processes in Japanese EFL Learners. (January 2020) - Terao, Takahiro; Ishii, Hidetoki
This study aimed to compare selection patterns of distractors (incorrect options) according to test taker proficiency regarding Japanese students' summarization skills of an English paragraph. Participants included 414 undergraduate students, and the test comprised three summarization process types—deletion, generalization, and integration. Within the questions, which represented summary candidates for a final version of a test, distractors were created reflecting typical student errors related to each summarization process. Six distractor types were tested. Results showed that distractors that were missing important information for the summary functioned well for determining low-, middle-, and high-proficiency students regarding deletion items. For generalization items, both distractor types, those containing examples and those with inappropriate superordinates, were attractive for low- and middle-proficiency students. Regarding integration items, it was found that distractors missing the author's viewpoint in the summary were more attractive only for less-proficient students. Several tips to guide future item writing are provided.